ANALISIS SARANA ALAT DAN BAHAN PRAKTIKUM LABORATORIUM BIOLOGI BERBASIS KOMPETENSI DASAR KURIKULUM 2013 PADA MATA PELAJARAN BIOLOGI KELAS XI SEMESTER II DI SMA SWASTA EDUCATION - Marweni Marweni; Arnentis Arnentis; Mariani Natalina L (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to analyze the tools and materials for the biology laboratory practicum based on the basic competencies of the 2013 curriculum in biology class XI semester II SMA Swasta Education. This type of research is descriptive research with quantitative methods. The preparation of research instruments was carried out at the Biology Education Study Program, Riau University. This research was conducted at the Education Private High School Pekanbaru. The time of this research is from August 3, 2021 to January 22, 2022. The data and data sources are researchers conducting laboratory observations, interviewing biology teachers and laboratory assistants. The data collection instruments in this study were observation sheets and interview sheets. Based on the results of data analysis, it is known that the tools and materials for biology laboratory practicum class XI semester II in SMA Swasta Education based on the Minister of National Education Regulation No. 24 of 2007 and No. 08 of 2018 is included in the good category, obtaining an average percentage of 77.33%. Meanwhile, the tools and materials for the biology laboratory practicum class XI semester II in SMA Swasta Education based on the basic competencies of the 2013 curriculum are included in the sufficient category to obtain an average percentage of 60.63%.Key Words: Analysis, Curriculum, Biology